ANALISA FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DEPRESI PADA PASIEN STROKE DI RUANG RAWAT INAP RSUD KABUPATEN KEDIRI - admin ilkes (STIKES Karya Husada Kediri, 2017)
Post-stroke depression is a mood disorder that can occur at any time after the stroke. It affects approximately 20-50% within the first year after stroke and peak incidence is estimated at 6 months post-stroke. The aim of this study was to analyze factors associated with the incidence of depression in stroke patients in the patient wards of hospitals district of Kediri. The study design used was descriptive analytic cross sectional approach. The population is all stroke patients in patient wards of hospitals district of Kediri. In from 11 until 30 January 2017. Sampling techniques performed by Accidental Sampling. A total of 17 respondents. The research instrument with a questionnaire and checklist, statistical test used was the regression test. Results of univariate analysis showed low education (41.2%), the elderly (47.1%), accompanied by comorbidities (58.8%), long-suffering stroke 6-9 days (47.1%) of family support optimal (76 , 5%) had moderate intellectual damage cognitive function (76.5%), impaired functional abilities require total assistance (41.2%) and depressed (76.5%). Results of bivariate analysis are statistically significant relationship between age and depression (p = 0.046), functional ability and depression (p = 0.034), comorbidities with depression (p = 0.023), cognitive function and depression (p = 0.005), duration suffered a stroke and depression (p = 0.021), whereas there was no significant relationship between education and depression (p = 0.234), between the support of families with depression (p = 0.654). The most dominant factor likely to trigger symptoms of depression is a factor in cognitive function by 4.143 times. This research is expected to be input for care institutions and educational institutions to improve the role of the family in minimizing factors that can lead to depression and can be used as a reference by further research.